PROSES REKRUTMEN DAN SELEKSI TERHADAP KINERJA KARYAWAN PADA PT SCHNEIDER ELECTRIC MANUFACTURING BATAM - Leli Sumanti Lubis; Nora Pitri Nainggolan (LPPM Universitas Putera Batam, 2019)
Human resourches is the most valuable asset in company. With a good recruitment and selection process, those will results high employee work Rate. Summary of the project are that we want to know correlation in partially and simultaneously within recruitment (X1) and selection (X2) process towards employee work rate at Schneider Electric Manufacturing Batam company. Based on the hypothesis analysis results of the influence of the process of recruitment and selection of employees performance in Schneider Electric Manufacturing Batam company, it seems that there is a positive and significant influence between the process of recruitment and selection towards employees' performance. This study uses causality and using multiple linear regression analysis. From the test results and data processing, it can be concluded that the process of recruitment to employee performance H1 and H2 is accepted. And test results of data processing to employee performance H3 selection is accepted.